Pengenalan Wisata Pancer Door Dengan Animasi 3 Dimensi - Hakim, Frestika Cahyo; Yulianto, Lies (APMMI - Asosiasi Profesi Multimedia Indonesia, 2014)
ABSTRACT Pancer Door is a stub at this point in the beach resort city of Pacitan. Therefore, the construction is done by stages. Means of promotion at the time was still using the Figure 2 dimensions, so that the results achieved are less than the maximum. With the 3-D animation is expected that in the future introduction of beach tourism and coastaltourism regional development more detail and clarity. The scope of the problem in this study is how to create multimedia-basedinformation media that can be used as a media introduction to the public beaches.The method used in the manufacture of multimedia-basedinformation is the media, library methods, observations, interviews, analysis, product design, testing and implementation. With the 3-Danimation is expected to potentially help the media and thepromotion of coastal tourism information.Keyword :